Resiliensi pada mahasiswa di Jakarta: Menilik peran komunitas - Kinanthi, Melok Roro; Grasiaswaty, Novika; Tresnawaty, Yulistin (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2020)
AbstractCollege students are prone to depression so that they need to be resilient. The aim of this study is to examine whether community resilience affects resiliency among college students in Jakarta. With a quantitative approach, this study involved 265 participants, selected by convenience sampling. We applied Community Advancing Resilience Toolkit Assessment Survey (CARTAS) and Connor Davidson Resilience Scale (CD-RISC) to gather data on the variables. Reliability coefficients for CARTAS were .656 to .806 for each dimension. While the reliability coefficient for CDRIS was .881. The regression analysis revealed community resilience has a significant positive contribution to individual resilience among participants. For each dimension, the contribution of community resilience to individual resilience was 7,9% to 12,2%. This result implied the community-based approach should be considered to develop an intervention for enhancing individual resilience.Keywords: College student; Community resilience; Resilience. AbstrakPenelitian terdahulu mengungkapkan bagaimana resiliensi memainkan peranan penting bagi mahasiswa agar dapat berdaya dengan maksimal. Penelitian ini bertujuan untuk mengetahui peran resiliensi komunitas terhadap resiliensi mahasiswa di Jakarta. Menggunakan pendekatan kuantitatif, penelitian ini melibatkan 265 partisipan yang dipilih melalui convenience sampling. Instrumen pengumpulan data yang digunakan adalah Community Advancing Resilience Toolkit Assessment Survey (CARTAS) and Connor Davidson Resilience Scale (CDRISC). Koefisien reliabilitas Cronbach Alpha CARTAS berkisar antara 0,656- 0,806 untuk tiap-tiap dimensinya. Sementara itu, koefisien reliabilitas Cronbach Alpha CDRISC adalah 0,881. Analisis regresi menunjukkan resiliensi komunitas berkontribusi positif secara signifikan terhadap resiliensi mahasiswa di Jakarta, dengan kontribusi sebesar 7,9% hingga 12,2%. Temuan ini mengindikasikan pendekatan berbasis masyarakat atau komunitas dapat dipertimbangkan dalam penyusunan intervensi yang dapat meningkatkan resiliensi individu.Kata kunci: Mahasiswa; Resiliensi komunitas; Resiliensi.